Les Effets Indésirables Digestifs De La Chimiothérapie : Cas Des Patients De L’institut National D’oncologie De Rabat (Maroc) - Mustapha Ahtit; Soulaymani abdelmajid; Khadmaoui Abderrazak; R. Benkirane; Soulaymani Bencheikh Rachida; E. Kerak (European Scientific Journal, ESJ, 2016)
An adverse reaction of an anticancer drug is a harmful and an unintended reaction by patient suffering from cancer disease who is often polymedicated. The treatment of cancers by anti-cancer molecules produces serious adverse drug effects. The main purpose of this paper is to present and evaluate the digestive adverse effects involved in anti-cancer drugs and their potential of correlation to anticipate, prevent and improve the quality of care of patient suffering from cancer disease. This is a prospective study that that enrolled 147 patients seen between January 25 and June 25, 2009 with adverse drug reactions due to an anticancer treatment. Breast and cavum cancers present 34% of cases. The average age was 46.52 years. The sex ratio (M / F) was 0.33. During the study period 283 Adverse drug effects of anticancer drugs were collected with a predominance (132) adverse digestive effects and 32 anticancer drugs were counted on all medical prescriptions. Nausea and vomiting are the most common side effects, sometimes very severe. The availability of anti-emetics in the family of 5-HT3 serotoninergic antagonists has considerably improved the experience of patients undergoing anticancer chemotherapy, hence the importance of pharmacovigilance as a tool is to improve the quality of anticancer care.